Pseudomonas aeruginosa Scleritis following Pterygium Surgery with Mitomycin C or Beta Irradiation: Three-Case Report - Winai Chaidaroon (Case Reports in Ophthalmological Medicine, 2022)
Purpose. To report three cases of culture-positive Pseudomonas aeruginosa scleritis following pterygium surgery. Patients and Methods. A retrospective study of all patients of Pseudomonas aeruginosa scleritis after pterygium surgery presented from May 2017 to May 2020 was performed. Patient demographics and clinical characteristics included age, gender, time between prior surgery and onset, adjunctive therapy, risk factors, initial visual acuity, final visual acuity, clinical features, medical treatment, and surgical intervention were analyzed. Results. Three eyes of three patients with clinical characteristics and laboratory-confirmed Pseudomonas aeruginosa scleritis were identified. Two patients were related with mitomycin C application after pterygium surgery, and only one had beta irradiation. Antibiotic administration and scleral debridement were required in 3 patients. One eye was enucleated. Final visual outcomes of two patients were improved. Conclusions. Pseudomonas aeruginosa scleritis after pterygium surgery is a crucial ophthalmic disease. An early diagnosis with a prompt intensive antibiotic treatment in combination with surgical interventions may improve visual outcome.